Investigating the causes of the recent Brazilian trade surpluses - Jo\~ao Victor Issler; Ricardo Costa Gazel (Institute for Applied Economic Research (ipea), 2015)
This paper investigates the recent boom od the Brazilian trade surplus by estimating a partial adjustment model for exports and imports. The results indicate that exports quantum is basically explained by the income of the rest of the world and by the gap of domestic output. The role of the exchange rate seemed to be negligible and sometimes contradictory vis-à-vis economic theory. The imports quantum depend solely on the evolution os the real exchange rate, and domestic output fluctuations did not impact imports.
Keywords: 330